Modelling the relationship between isokinetic muscle strength and sprint running performance - Dowson, M. N.; Nevill, M. E.; Lakomy, H. K.; Nevill, A. M.; Hazeldine, R. J. (Journal of Sports Sciences, 1998)
he aim of this study was to examine the relationship in elite performers of isokinetic muscle strength across three lower limb joints and sprinting performance, including the use of theoretical models. Eight rugby players, eight track sprinters and eight competitive sportsmen, all elite national or regional competitors, performed sprints over 15 m and 35 m with times recorded over 0–15 m and 30–35 m. Isokinetic torque was measured at the knee, hip and ankle joints at low (1.05 rad s −1), intermediate (2.09 or 2.62 rad s −1) and high (3.14 or 4.19 rad s −1) speeds during concentric and eccentric muscle actions. Using linear regression and expressing sprint performance as time, the strongest relationship, for the joint actions and speeds tested, was between concentric knee extension at 4.19 rad s −1 and sprint performance (0–15 m times: r = −0.518, P < 0.01; 30–35 m times: r = −0.688, P < 0.01). These relationships were improved for 0–15 m, but not for 30–35 m, by expressing torque relative to body mass (0–15 m times: r = −0.581; 30–35 m times: r = −0.659). When 0–15 m performance was expressed as acceleration rather than time, the correlation was improved slightly ( r = 0.590). However, when the data (0–15 m times) were fitted to the allometric force model proposed by Gunther, 77% of the variance in concentric knee extension torque at 4.19 rad s −1 could be explained by 0–15 m times, limb length (knee to buttocks) and body mass. The fitted parameters were similar to those from the theoretical model. These findings suggest that the relationship between isokinetic muscle strength and sprint performance over 0–15 m (during the acceleration phase) is improved by taking limb length and body mass into account.